Environmental consultancy: dancing bee bioindicators to evaluate landscape “health” - Couvillon, Margaret J.; Ratnieks, Francis L. W. (Frontiers in Ecology and Evolution, 2015)
Here we explore how waggle dance decoding may be applied as a tool for ecology by evaluating the benefits and limitations of the methodology compared to other existing ways to evaluate the honey bees’ use of the landscape. The honey bee foragers sample and “report” back on large areas (c. 100km2). Because honey bees perform dances only for the most profitable resources, these data provide spatial information about the availability of good quality forage for any given time. We argue that dance decoding provides information for a wide range of ecological, conservation, and land management issues. In this way, one species and methodology gives us a novel measure of a landscape’s profitability and “health” that may be widely relevant, not just for honey bees, but for other flower-visiting insects as well.